1991
DOI: 10.1212/wnl.41.7.1015
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic complications of infective endocarditis

Abstract: Neurologic syndromes often complicate the management of infective endocarditis (IE). We retrospectively reviewed 166 episodes of native valve endocarditis to assess the occurrence and implications of nonfocal encephalopathy, meningitis, salient headache, back pain, and brain abscess. Neurologic complications occurred in 35% (58/166) of patients: 41% (54/133) of mitral or aortic valve IE and 12% (4/33) of tricuspid valve IE. Of 133 cases of mitral or aortic valve IE, encephalopathy occurred in 14%, meningitis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
2
15

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(76 citation statements)
references
References 0 publications
7
52
2
15
Order By: Relevance
“…1,3,8 Some increase was noted compared to the studies before the pre-antibiotic era, and this may reflect the improved survival rate in patients with IE with antibiotic cover and early surgical intervention as needed, so neurological complications have more time to appear. Aortic valve disease in our patients was more associated with neurological complications, and this differs from other studies that showed a linkage between mitral valve disease and increased risk of cerebral embolism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,3,8 Some increase was noted compared to the studies before the pre-antibiotic era, and this may reflect the improved survival rate in patients with IE with antibiotic cover and early surgical intervention as needed, so neurological complications have more time to appear. Aortic valve disease in our patients was more associated with neurological complications, and this differs from other studies that showed a linkage between mitral valve disease and increased risk of cerebral embolism.…”
Section: Discussionmentioning
confidence: 99%
“…2 Intracranial hemorrhage is identified in 5% of cases 6 and cerebral infarctions in 14%-19% 3,5,7 other complications include acute meningitis, brain abscess, encephalopathy, seizures and headache. 1,3,5 Rarely, back pain with root lesion due to intervertebral disc infection or acute mononeuropathy may occur. 1,3 Despite the introduction of potent antimicrobial agents and new diagnostic and therapeutic procedures, the neurological complications remain high.…”
Section: Sas Khan Ba Yaqub Sm Al Deeb Neurological Complications Omentioning
confidence: 99%
See 2 more Smart Citations
“…In adults with infective endocarditis, neurological complications develop in 20 -40% of patients [4]. The most frequent neurological complications include cerebral infarction, bacterial meningitis, intracerebral hemorrhage and mycotic aneurysms [5,6].…”
Section: Introductionmentioning
confidence: 99%